Practical aspects of open government data projects - Pastor-Sánchez, Juan-Antonio (Anuario ThinkEPI, 2014)
Publishing open data managed by public administrations is beginning to be considered a strategic action for social and economic development. The legislative and policy support on this issue should be complemented by practical considerations related to certain technical aspects. These aspects have a nimpact on the descriptive metadata datasets of specialized catalogs, the use of open formats and the need to consider open data projects in the cycle of information in organizations. Open data is a source of innovation and new business models that requires efficient mechanisms for locating datasets and tools to access and reuse them.